Reseña de Casas Gómez, M. (dir.), Díaz Hormigo, MA T. (ed.) (1998), III Jornadas de Lingüística. (In memoriam Profesor Emilio Alarcos Llorach); Cádiz, Servicio de Publicaciones de la Universidad de Cádiz. - Varo Varo, Carmen (Pragmalingüística, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Casas Gómez, M. (dir.), Díaz Hormigo, MA T. (ed.) (1998), III Jornadas de Lingüística. (In memoriam Profesor Emilio Alarcos Llorach); Cádiz, Servicio de Publicaciones de la Universidad de Cádiz.